ANALISIS KUALITAS PELAYANAN DAN KUALITAS VARIAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KANTIN SEKOLAH YAYASAN BUDI MULIA - Faturrohman, M. Fadhlan; Shinta Lestari, Deara; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2024)
a canteen is a place or room for selling and serving food and drinks, usually in schools, campuses, offices, factories or other public places. The main function of the canteen is to serve food and drinks so that employees, students and visitors do not need to leave the place to look for food. Visitors are often offered a variety of food and drinks at relatively affordable prices. The dining room is not just a place to eat, but is often also a place where visitors gather and gather. Cafeterias in schools and campuses are popular places for students to gather and rest between classes. The data analysis technique for measuring the variables in this research uses SPSS software, by entering the results of the operationalization of the variables to be tested.